2020
DOI: 10.3390/jcm9092848
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-Year Outcomes between Intravitreal Ranibizumab and Intravitreal Aflibercept for Diabetic Macular Edema with “Treat-and-Extend” Regimen—Its Usefulness and Problems

Abstract: Background: To compare the effectiveness of intravitreal ranibizumab (IVR) and intravitreal aflibercept (IVA) performed with the treat-and-extend (TAE) regimen on eyes with diabetic macular edema (DME). Patients and methods: This is a retrospective study of 125 eyes of 125 treatment-naïve DME patients who received anti-VEGF injections at three consecutive monthly intervals as the loading phase. The changes in the best-corrected visual acuity (BCVA), central retinal thickness (CRT), diabetic retinopathy severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The mean number of injections for ranibizumab 1 dose at baseline (RAN 1q4w) followed by an as-needed approach (pro re nata [PRN]) ranged from 3.9 37 to 4.4, 29 and the mean number of injections for ranibizumab 3q4w (RAN 3q4w) followed by PRN regimen ranged from 4.3 41 to 7.2. 36 Only 1 study reported the mean number of injections for RAN 3q4w followed by treat and extend (T&E) regimen (7.1) 42 at the 12-month follow-up ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean number of injections for ranibizumab 1 dose at baseline (RAN 1q4w) followed by an as-needed approach (pro re nata [PRN]) ranged from 3.9 37 to 4.4, 29 and the mean number of injections for ranibizumab 3q4w (RAN 3q4w) followed by PRN regimen ranged from 4.3 41 to 7.2. 36 Only 1 study reported the mean number of injections for RAN 3q4w followed by treat and extend (T&E) regimen (7.1) 42 at the 12-month follow-up ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…For aflibercept, 4 studies reported injection frequency at the 12-month follow-up (range: 2.9 35 to 6.5 42 ). The cumulative mean number of injections was 4.6 (4 studies with 5 treatment arms).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An OCT-guided treat-and-extend management protocol was used during this study, similar in design to what has been widely adopted in the real world. 5 , 6 In short, patients underwent monthly (28–34 days) anti-VEGF treatments until all identifiable retinal edema had resolved on OCT. Once the retinal edema had resolved, patients were extended out to 1–2 week increments until recurrence of the retinal edema was observed, and the interval of treatment was then adjusted to maintain a macula that was fluid-free. For the purpose of this study, patients were considered treatment-resistant whenever a fluid-free macula on OCT could not be accomplished in spite of more than or equal to six anti-VEGF treatments over a 12-month period.…”
Section: Methodsmentioning
confidence: 99%